2021
DOI: 10.1038/s41598-020-80823-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional anatomy, computed tomography, and magnetic resonance imaging of the banded houndshark (Triakis scyllium)

Abstract: Due to their important phylogenetic position among extant vertebrates, sharks are an invaluable group in evolutionary developmental biology studies. A thorough understanding of shark anatomy is essential to facilitate these studies and documentation of this iconic taxon. With the increasing availability of cross-sectional imaging techniques, the complicated anatomy of both cartilaginous and soft tissues can be analyzed non-invasively, quickly, and accurately. The aim of this study is to provide a detailed anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Other studies have pursued similar endeavours of providing anatomical studies aided by modern imaging techniques [ 36 , 37 ], but, to our knowledge, none of these have included three-dimensional or otherwise interactive representations. One noteworthy online resource for chondrichthyan anatomy is the website ‘Chondrichthyan Tree of Life’ [ 38 ] which, among other things, offers an impressive selection of less in-depth segmented anatomical models than the one presented in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have pursued similar endeavours of providing anatomical studies aided by modern imaging techniques [ 36 , 37 ], but, to our knowledge, none of these have included three-dimensional or otherwise interactive representations. One noteworthy online resource for chondrichthyan anatomy is the website ‘Chondrichthyan Tree of Life’ [ 38 ] which, among other things, offers an impressive selection of less in-depth segmented anatomical models than the one presented in this article.…”
Section: Introductionmentioning
confidence: 99%
“…In research contexts, however, MRI of live fish has already been successfully implemented in a number of species (Wu et al 2015; Koth et al 2017). The MRI characterization of normal anatomy in koi, as well as other aquatic species, has already begun to be established, which further increases the utility of the modality (Kalat and Shabanipour 2010; Ziegler et al 2011; Kim et al 2021). To our knowledge, there are no prior reports of MRI usage as an ante‐mortem diagnostic for fish in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies conducted to date in aquatic animals, such as various dolphins (Alonso‐Farré et al, 2014, 2015; Ivančić et al, 2014), California sea lion Zalophus californianus (Dennison & Schwarz, 2008), Loggerhead sea turtle Caretta caretta (Valente et al, 2007), and Pacu Colossoma macroponum (Carr et al, 2014), have compared anatomical cross‐sections and CT images. With regard to Selachimorpha, Kim et al (2021) reported the use of NCCT and MRI to study the cadavers of Banded houndshark Triakis scyllium for the purpose of the normal anatomy reference. These authors reported that from the NCCT images of soft tissues, it was difficult to identify the adjacent organs because of low contrast, although sufficient images were obtained by MRI scan.…”
Section: Introductionmentioning
confidence: 99%